Fermentation to Increase the Value of Roasted Coffee Silverskin as a Functional Food Ingredient - Nadia Guzińska; Maria Dolores del Castillo; Edyta Kordialik-Bogacka (Foods)
Roasted coffee silverskin (RCSS) is a by-product of coffee production characterized by its content of phenolic compounds, both free and bound to macromolecules. In this study, RCSS was fermented to release these compounds and consequently increase its value as a functional food ingredient. Fermentation was carried out using yeast, acetic acid bacteria, and lactic acid bacteria, either as single strains or as a designed microbial consortium. The latter included Saccharomycodes ludwigii, Gluconobacter oxydans, and Levilactobacillus brevis, mimicking a symbiotic culture of bacteria and yeast commonly used in kombucha fermentation (SCOBY). This symbiotic microbial culture consortium demonstrated notable efficacy, significantly enhancing the total phenolic content in RCSS, with values reaching 14.15 mg GAE/g as determined by the Folin–Ciocalteu assay and 7.12 mg GAE/g according to the Fast Blue BB method. Antioxidant capacity improved by approximately 28% (ABTS) and 20% (DPPH). Moreover, the fermented RCSS supported the viability of probiotic strains (Saccharomyces boulardii SB01 and Levilactobacillus brevis ŁOCK 1152) under simulated intestinal conditions. These results suggest that RCSS, particularly after fermentation with a full symbiotic microbial culture consortium, has strong potential as a clean label, zero-waste functional food ingredient.